Recurrent Reverse Evolution Maintains Polymorphism after Strong Bottlenecks in Commensal Gut Bacteria - Sousa, Ana (2017)
The evolution of new strains within the gut ecosystem is poorly understood. We used a natural but controlled system to follow the emergence of intraspecies diversity of commensal Escherichia coli, during three rounds of adaptation to the mouse gut (∼1,300 generations). We previously showed that, in the first round, a strongly beneficial phenotype (loss-of-function for galactitol consumption; gat-negative) spread to >90% frequency in all colonized mice. Here, we show that this loss-of-function is repeatedly reversed when a gat-negative clone colonizes new mice. The regain of function occurs via compensatory mutation and reversion, the latter leaving no trace of past adaptation. We further show that loss-of-function adaptive mutants reevolve, after colonization with an evolved gat-positive clone. Thus, even under strong bottlenecks a regime of strong-mutation-strong-selection dominates adaptation. Coupling experiments and modeling, we establish that reverse evolution recurrently generates two coexisting phenotypes within the microbiota that can or not consume galactitol (gat-positive and gat-negative, respectively). Although the abundance of the dominant strain, the gat-negative, depends on the microbiota composition, gat-positive abundance is independent of the microbiota composition and can be precisely manipulated by supplementing the diet with galactitol. These results show that a specific diet is able to change the abundance of specific strains. Importantly, we find polymorphism for these phenotypes in indigenous Enterobacteria of mice and man. Our results demonstrate that natural selection can greatly overwhelm genetic drift at structuring the strain diversity of gut commensals and that competition for limiting resources may be a key mechanism for maintaining polymorphism in the gut.